2020
DOI: 10.1016/j.ijantimicag.2020.106202
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue inhibits replication of SARS-CoV-2 in vitro

Abstract: Highlights Methylene blue 50% cytotoxicity concentration (CC 50 ) > 100 µM in Vero E6 cells. Methylene blue EC 50 of 0.3 ± 0.03 µM and EC 90 of 0.75 ± 0.21 µM at MOI of 0.25 against Vero E6 cells infected with SARS-CoV-2 strain (IHUMI-3). In comparison, EC 50 and EC 90 of 1.5 and 3.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 36 publications
2
59
0
1
Order By: Relevance
“…For example, one group found that MeBlu showed virucidal activity at low micromolar concentrations when incubated with Vero E6 cells and SARS-CoV-2 for 20 h in the dark ( Cagno et al, 2020 ). Another group also found non-photoactivated MeBlu to inhibit SARS-CoV-2 replication in Vero E6 in vitro with an IC 50 of 0.3 ± 0.03 μM at multiplicity of infection (MOI) of 0.25 ( Gendrot et al, 2020 ). The ability of MeBlu to inhibit the SARS-CoV-2-S–ACE2 PPI could be a mechanism of action contributing to such activity especially as we also showed MeBlu to inhibit the entry of SARS-CoV-2 pseudovirus into ACE2-expressing cells with low micromolar IC 50 ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one group found that MeBlu showed virucidal activity at low micromolar concentrations when incubated with Vero E6 cells and SARS-CoV-2 for 20 h in the dark ( Cagno et al, 2020 ). Another group also found non-photoactivated MeBlu to inhibit SARS-CoV-2 replication in Vero E6 in vitro with an IC 50 of 0.3 ± 0.03 μM at multiplicity of infection (MOI) of 0.25 ( Gendrot et al, 2020 ). The ability of MeBlu to inhibit the SARS-CoV-2-S–ACE2 PPI could be a mechanism of action contributing to such activity especially as we also showed MeBlu to inhibit the entry of SARS-CoV-2 pseudovirus into ACE2-expressing cells with low micromolar IC 50 ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent study compared the in vitro median Effective Concentration (EC50) of 3 drugs against SARS-COV-2, when administered 4h post infection. MB was the most efficient antiviral drug with an EC50 of 0.30 ± 0.03 µM, followed by Hydroxychloroquine (1.5 ± 0.3 µM) and Azithromycin (20.1 ± 4.5 µM) (16). In view of the wide variety of singlet oxygen driven chemical reactions corroding nucleic acids and proteins, one is surprised by the well documented absence of severe side effects of MB, even at doses up to 5 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…As the risk of COVID-19 spreading in dental care is very high, it is fundamental to emphasize the importance of improving and complementing the oral disinfection procedures, especially since many infected patients present as asymptomatic condition. Previous studies confirm the effectiveness of aPDT for microbiological oral disinfection [ 13 ], and in vitro antiviral activity against SARS-CoV-2 [ 10 , 11 ]. As result, an oral disinfection protocol using mouthwashes containing a specific photosensitizer activated by a precise wavelength could be performed to reduce the spread of COVID-19 in dental offices.…”
mentioning
confidence: 57%
“…When dealing with alternative disinfection methods, Antimicrobial Photodynamic Therapy (aPDT) has been shown to be effective against enveloped viruses [ 10 , 11 ], as well as in the treatment of pneumonia and/or respiratory tract infections, and the disinfection of the oral cavity [ [12] , [13] , [14] ]. In this sense, aPDT can also be an effective method against SARS-CoV-2, because in addition to promoting damage to the virus by the generation of reactive oxygen species (ROS) [ 10 , 11 , 15 ], it prevents the penetration of microorganisms in the mucous membranes, thereby controlling the occurrence of secondary infections [ 14 ]. aPDT becomes even more advantageous considering the SARS-CoV-2 mutation capacity, as aPDT is a method that does not trigger microbial resistance mechanisms [ 14 , 16 , 17 ].…”
mentioning
confidence: 99%